TOWARDS AUTOMATION IN PORTS; THE INFLUENCE ON SAFETY CULTURE. - Mitriaka, Nancy (My University, 2024)
It is essential to understand that the increasing expansion of global trade and globalisation of the world economy lead to an increasing use of equipment in the maritime industry which raised the need for automation in port operation. In this master thesis the qualitative and quantitative approaches are combined in mixed method and triangulation. The data are both primary in the form of interviews, questionnaires and observations, which are presented in the result and analysis chapter and secondary, in the form of literature review analysis. The purpose of this master thesis is to explore the influence of automation on safety management culture used in Ro-Ro shipping ports by a liner shipping company. Linked to this purpose, this thesis aims to address the impacts of further implementation of automation in reputation and economic indicators for the liner shipping company, which will have further effects in economic and social sustainability of the company. To succeed this, a further implementation of automation in liner shipping companies will occur in a possible need of a structured Safety Management System (SMS) and proactive risk assessment process to maintain the company’s efficiency and employees’ safety. The results highlight that these safety measures would not only boost employees' spirit and motivation, but also would be positive to the company's reputation and overall performance. As liner shipping companies move towards transforming their operations to automation, it is important to implement a consolidated SMS and proactive risk assessment process to increase safety, efficiency, productivity, and economic sustainability. The connection among safety, automation and social sustainability indicated the importance of involving the employees in the transformation journey.
Keywords: Liner Shipping Company; Trailer Operations; Ro-Ro port; Port Operations; Safety Culture; Safety Management Systems; Risk Assessment; Automation; Social Sustainability; Economic Sustainability